The Genus citrus - Talon, Manuel; Caruso, Marco; Gmitter, Fred G. (Woodhead Publishing, an imprint of Elsevier, 2020)
The Genus Citrus presents the enormous amount of new knowledge that has been generated in recent years on nearly all topics related to citrus. Beginning with an overview of the fundamental principles and understanding of citrus biology and behavior, the book provides a comprehensive view from Citrus evolution to current market importance. Reporting on new insights supported by the elucidation of the citrus genome sequence, it presents groundbreaking theories and fills in previous knowledge gaps. Because citrus is among the most difficult plants to improve through traditional breeding, citrus researchers, institutions and industries must quickly learn to adapt to new developments, knowledge and technologies to address the biological constraints of a unique fruit-tree such as citrus. Despite the challenges of working with citrus, tremendous progress has been made, mostly through advances in molecular biology and genomics. This book is valuable for all those involved with researching and advancing, producing, processing, and delivering citrus products. --